2015
DOI: 10.1007/s10295-015-1592-y
|View full text |Cite
|
Sign up to set email alerts
|

The Methanosarcina acetivorans thioredoxin system activates DNA binding of the redox-sensitive transcriptional regulator MsvR

Abstract: The production of biogas (methane) by anaerobic digestion is an important facet to renewable energy, but is subject to instability due to the sensitivity of strictly anaerobic methanogenic archaea (methanogens) to environmental perturbations, such as oxygen. An understanding of the oxidant-sensing mechanisms used by methanogens may lead to the development of more oxidant tolerant (i.e. stable) methanogen strains. MsvR is a redox-sensitive transcriptional regulator that is found exclusively in methanogens. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…However, it has also been investigated significantly in the anaerobic organisms (6 -24) focusing on both the characteristics of the Trxs and TrxRs (6,8,9,(11)(12)(13)(15)(16)(17)(18)(19)(20)(21)(22)(23) and their physiological roles (6,7,10,14,20). For example, the isolation of the putative Trx targets via Trxaffinity chromatography and the results from activation assays with select purified and deactivated enzymes have established that in Chlorobaculum tepidum, a green sulfur bacterium and an anaerobic phototroph, the thioredoxin system implements post-translational control on the tricarboxylic acid or the TCA cycle and sulfur metabolism and assists in the defense against oxidative stress (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has also been investigated significantly in the anaerobic organisms (6 -24) focusing on both the characteristics of the Trxs and TrxRs (6,8,9,(11)(12)(13)(15)(16)(17)(18)(19)(20)(21)(22)(23) and their physiological roles (6,7,10,14,20). For example, the isolation of the putative Trx targets via Trxaffinity chromatography and the results from activation assays with select purified and deactivated enzymes have established that in Chlorobaculum tepidum, a green sulfur bacterium and an anaerobic phototroph, the thioredoxin system implements post-translational control on the tricarboxylic acid or the TCA cycle and sulfur metabolism and assists in the defense against oxidative stress (7).…”
mentioning
confidence: 99%
“…Recently, a proteomics study has shown that there is clear potential for a Trx-based global redox regulation of metabolism, including methanogenesis, in Methanocaldococcus jannaschii, a strictly anaerobic and deeply rooted hyperthermophilic methanogenic archaeon that lives in deep-sea hydrothermal vents (20). Two reports also describe the activation of deactivated methanogen proteins by thioredoxin (10,20).…”
mentioning
confidence: 99%
“…In M. acetivorans, treatment of MsvR with H 2 O 2 results in oxidation of cysteine thiols, preventing binding of MsvR to promoters. Incubation of oxidized MsvR with the M. acetivorans TRX system, consisting of NADPH, TRX reductase and one of the 7 TRXs, leads to reduction of the cysteines and binding to its own promoter [111].…”
Section: Thiol/disulfide Switches In Archaeamentioning
confidence: 99%
“…M. acetivorans was shown to possess a single thioredoxin reductase TrxR and seven Trx homologues (Trx1-7), at least three of which are functional (McCarver and Lessner, 2014). In this regard, it has previously been shown that the Trx system is able to reduce disulfides back to thiols in the redox-sensitive transcriptional regulator MsvR of M. acetivorans (Sheehan et al, 2015).…”
Section: A Thiol/disulfide Switch Regulates Kinase Activitymentioning
confidence: 99%